BIOLOGI DALAM ALQURAN PERSPEKTIF SAINS - Amin Maulana Maksum; Mohd Yakub Zulkifli; Mohamed Akhiruddin Ibrahim; Azniwati Abdul Aziz; Abu Bakar Bin Hud Yahya Bakar Bin Hud Yahya (UIN Siber Syekh Nurjati Cirebon, 2017)
It is the Qur'an as a book that God decides s.w.t certainly has many uniqueness. He includes privileges in various disciplines that are useful for human use. They are biological sciences that study the structure, function, growth, origin, evolution and sprinkling of living things. In general, biological science is divided into several fields including anatomy, biophysics, biogeography, biochemistry, marine biology, molecular biology, cell biology, botany, biotechnology, physiology, microbiology, paleontology, pathology, virology and zoology. In the Qur'an there are several signs that indirectly show the relation of several fields in this field of biology. The application of modern science to it has succeeded in revealing the uniqueness of several issues that have been stated in this holy book from a scientific perspective. This study presents a number of examples of the Qur'anic verses which are seen from the point of view of several fields of biology that have been stated. The related verse is translated and then reviewed based on findings from scientific studies conducted by investigators. The results of the study show that there are many verses that have been revealed by Allah. This gives a signal to the uniqueness of many fields in biology, after studies and observations by modern-day investigators.